Effect of bleaching light on measurements of lateral diffusion in cell membranes by the fluorescence photobleaching recovery method. - Wolf, D E (1980)
The Fc receptors for IgE on rat basophil leukemia 2H3 cells were labeled with either rhodamine- or fluorescein-conjugated IgE and then with Fab fragments of anti-IgE conjugated with the other dye. Fluorescence photobleaching recovery measurements of lateral diffusion were performed with one of the dyes before and after extensive bleaching of the other dye over an entire cell. Bleaching one dye did not affect subsequent measurements made with the other dye. We thus detect no evidence for photoinduced artifacts in fluorescence photobleaching recovery experiments.